The Effect of Electroacupuncture and Gua Sha on Reducing Pain Scale and Neck Disability in Neck Pain Cases at Siligita Husada Independent Acupuncture Practice - Putra, I Nyoman Rama Saitri; Badri, Sholichan; Nugraha, Nurtama Aditya (HAKTI : Indonesian Acupuncture Therapists Association, 2025)
Neck pain is one of the musculoskeletal disorders due to several causative factors, one of which is ergonomic factors at work. Electroacupuncture and gua sha therapy have been widely used as alternative treatment methods to help reduce pain and improve functional ability in neck pain. This study aims to determine the effect of electroacupuncture and gua sha on reducing pain scale and neck disability. This study employed a double-blind randomized controlled trial (RCT) with a true experimental design. A total of 34 subjects were selected using simple random sampling from a population of 40, with 6 additional participants prepared as reserves. The intervention group received electroacupuncture at points GB 20 (Fengchi), GB 21 (Jianjing), and Gua Sha, while the control group received only electroacupuncture at GB 20 and GB 21. Pain intensity and neck disability were measured using the Numeric Rating Scale (NRS) and Neck Disability Index (NDI) before and after 10 sessions of therapy. Data were analyzed using univariate and bivariate tests, including tests of normality, homogeneity, and hypothesis testing, to assess the effectiveness of the interventions. Both the intervention group (electroacupuncture combined with Gua Sha) and the control group (electroacupuncture only) showed a significant reduction in pain intensity and neck disability, as measured by the NRS and NDI scores (p < 0.05). However, the reduction was greater in the intervention group, indicating a more pronounced effect when Gua Sha was added to electroacupuncture therapy. combination of electroacupuncture with Gua Sha provides greater clinical benefits compared to electroacupuncture alone